Fun mom dinner [videorecording (DVD)] - Aselton, Katie, 1978-; Collette, Toni; Everett, Bridget; Shannon, Molly, 1964-; Scott, Adam, 1973-; Huebel, Rob; Levine, Adam, 1979-; Rust, Paul, 1981- (Momentum Pictures, 2017)
Four moms, whose only common ground is their kids' preschool class, decide to get together for a harmless dinner. The night begins as a disaster, but the women quickly discover that they have more in common than they thought.